Animal exploitation at ed‐Dur (Umm al‐Qaiwain, United Arab Emirates). (May 2017) - Van Neer, Wim; Gautier, Achilles; Haerinck, Ernie; Wouters, Wim; Kaptijn, Eva
Abstract : Faunal remains are described from a series of contexts excavated in the coastal site of ed‐Dur, dated between the second and fourth century AD. The more than 19, 000 identified animal bones allowed a diachronic and spatial analysis. Subsistence relied heavily on domestic animals, in particular sheep and goat, and on fishing. Whereas the exploitation of terrestrial resources seems to have been quite constant throughout the period considered, the aquatic fauna shows changes through time. A shift, possibly linked to overexploitation, is seen both in the proportions of the targeted fish species and in their sizes. The deposition of some of the mammals encountered in burials is also dealt with; dog and ovicaprid can probably be added to the list of mammals used in ritual context in the region. Spatial analysis did not reveal particular concentrations or activity areas. In general the finds fit nicely in the archaeozoological record of the wider region.